Some Mathematical Reasoning on the Artificial Force Induced Reaction Method. Issue 7 (2nd December 2019) - Quapp, Wolfgang; Bofill, Josep Maria
Abstract : There are works of the Maeda–Morokuma group, which propose the artificial force induced reaction (AFIR) method (Maeda et al., J. Comput. Chem. 2014, 35, 166 and 2018, 39, 233). We study this important method from a theoretical point of view. The understanding of the proposers does not use the barrier breakdown point of the AFIR parameter, which usually is half of the reaction path between the minimum and the transition state which is searched for. Based on a comparison with the theory of Newton trajectories, we could better understand the method. It allows us to follow along some reaction pathways from minimum to saddle point, or vice versa. We discuss some well‐known two‐dimensional test surfaces where we calculate full AFIR pathways. If one has special AFIR curves at hand, one can also study the behavior of the ansatz. © 2019 The Authors. Journal of Computational Chemistry published by Wiley Periodicals, Inc. Abstract : Artificial force induced reaction (AFIR) points on a two‐dimensional surface are blue. In black color are drawn minimums and saddles of index one. The AFIR points explore quite good the reaction pathways from a reactant minimum over an intermediate to a product minimum. Only near the intermediate minimum, the connection has a gap. Red points depict maximums of the AFIR parameter.